Case Report: Life-threatening overlap of hemophagocytic syndrome and atypical hemolytic uremic syndrome in a patient with autoimmune polyglandular syndrome type 1 successfully treated with targeted immunotherapy - Coppola, Emma; Giardino, Giuliana; Romano, Roberta; Capalbo, Donatella; Italiani, Paola; Boraschi, Diana; De Rosa, Antonio; Toriello, Elisabetta; Palatucci, Annateresa; Rubino, Valentina; Ruggiero, Giuseppina; Salerno, Mariacarolina; et al. (Frontiers in Immunology, 2025)
BackgroundAutoimmune polyglandular syndrome type 1 (APS-1) is a rare inborn error of immunity caused by mutations in the AIRE gene, typically associated with chronic mucocutaneous candidiasis, hypoparathyroidism, and adrenal insufficiency. We report the first known case of APS-1 complicated by a life-threatening combination of secondary hemophagocytic lymphohistiocytosis (sHLH) and atypical hemolytic uremic syndrome (aHUS), successfully treated with targeted and supportive therapies.Case reportA 16-year-old female with a diagnosis of APS-1 confirmed by the presence of the nonsense variant c.415C>T (R139X) in exon 3 and the Finnish major mutation c.769C>T (R257X) in exon 6 of the AIRE gene presented with fever, cytopenias, organomegaly, and hyperferritinemia, fulfilling criteria for sHLH. Despite immunosuppressive therapy, she developed acute kidney injury, thrombocytopenia, and microangiopathic hemolytic anemia, consistent with aHUS. Treatment with the IL - 1 receptor antagonist anakinra and the complement inhibitor eculizumab led to rapid resolution of systemic inflammation and progressive renal and hematological recovery.ConclusionsHLH is an exceptionally rare complication in APS-1 and has so far been reported in only one patient with a combined EBV and SARS-CoV-2 infection. aHUS has never been described in patients with APS-1. This case highlights the potential for hyperinflammatory and complement-mediated complications in APS-1, supporting the hypothesis of a cytokine storm syndrome that bridges features of sHLH and aHUS. It broadens the known spectrum of immune dysregulation in APS-1 and underscores the importance of early recognition and combined immunomodulatory treatment in similar clinical scenarios.